Pertumbuhan Kunyit Putih (Curcuma zedoaria Rosc.) yang Diinokulasi Fungi Mikoriza Arbuskula Hasil Isolasi Dari RizosfirHornstedtia scyphifera Steud. - Marta Linda; Zozy Aneloi Noli; M. Idris (Jurnal Biologi Universitas Andalas, 2014)
A study on growth of turmeric (Curcuma zedoaria Rosc.) inoculated with Arbuscular Mycorrhizzal Fungi (AMF) isolated from the rhizosphere of Situngkek (Hornstedtia scyphifera Steud.) was done from March to August 2013 in the wire house and in Plant Physiology Laboratory, Department of Biology, Faculty of Natural Sciences, Andalas University. The aim of this study was to determine the growth of white turmeric inoculated with several doses of AMF. The experiment used Completely Randomized Design (CRD) with five treatments, control (A) and four replications. The inoculation doses were 10 g / Plant AMF (B), 20 g / plant AMF (C), 30 g / Plant AMF (D), 40 g / Plant AMF (E), 50 g / Plant AMF (F). The results showed that AMF inoculation gave no significant effect on plant height, number of leaf, leaf width and dry weight of turmeric. The highest root infection was 30 gr/plant (74.83 %). Generally, turmeric plant have a dependency on FMA inoculation with less and sufficient criteria of Habte and Manjunath. Keyword: Curcuma zedoaria, Mycorrhizal, Growth.